Gold(i)-catalyzed diastereo- and enantioselective [4 + 3] cycloadditions: construction of functionalized furano-benzoxepins. Issue 19 (30th August 2022) - Wang, Xunhua; Lv, Ruifeng; Li, Xiaoxun
Abstract : Highly diastereo- and enantioselective [4 + 3] cycloadditions of 2-(1-alkynyl)-2-alken-1-ones with o -QMs have been realized via a simple chiral gold catalysis, providing facile access to various functionalized furano-benzoxepins. Abstract : Enantioselective higher-order cycloaddition involving gold-furyl 1, 3-dipoles is an attractive but challenging transformation for the construction of chiral polycyclic medium-sized rings from readily available building blocks. Here, gold-catalyzed asymmetric [4 + 3] cycloadditions of 2-(1-alkynyl)-2-alken-1-ones with ortho -quinone methides are reported. A diverse range of functionalized tetrahydro-1-benzoxepins bearing the furan motif have been expediently prepared in good yields with high stereoselectivities (41 examples, up to 95% yield, all >20 : 1 dr, up to 97% ee). The reaction features mild reaction conditions with a broad scope, enabling the late-stage functionalization of important bioactive molecules. Moreover, the enantioenriched benzo[ b ]oxepin products could be transformed into various substituted furan derivatives.